Constraints on and facilitators of young people’s participation: The case of border regions of mainland Portugal - Marques da Silva, Sofia; Martins da Silvaa, Nicolas; Arezes, Sara; Sérgio Martins, Paulo; Faria, Sara; Dias, Vitor; Milheiro Silva, Ana (JSSE - Journal of Social Science Education, 2023)
Highlights: Young people are involved in diverse types of participation, being engaged, disengaged or unpolitical. Young people perceive opportunities to organise initiatives but not to participate in local decisions. Constraints on participation and responses to promote it were identified. Context-specific barriers were mentioned by young people and policymakers. Municipalities and schools are priority contexts for fostering youth participation. Purpose: This article aims to assess constraints on and facilitators of youth participation in rural border regions. Knowledge about regional participation of young people is useful for developing territorialised policies. Methodology: Using a mixed method approach designed in line with theories of civic and political participation and youth studies, we analysed responses from young people to a questionnaire (n = 3968) and interviews with policymakers (n = 36) and young people (n = 20). Findings: Young people are involved in diverse types of civic and political participation and perceive more opportunities to organise initiatives than to participate in local decision-making. Constraints on participation relate to the distance between politics, governance institutions and young people, weak strategies of municipalities, lack of youth organisations and mobility. Facilitators of participation include supporting youth-led activities or involving young people in local decisions. Research implications: the study contributes to understanding youth participation in rural regions.